2016
DOI: 10.1177/0269216316649155
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life outcome measures in paediatric palliative care: A systematic review of psychometric properties and feasibility of use

Abstract: Background:The number of children worldwide requiring palliative care services is increasing due to advances in medical care and technology. The use of outcome measures is important to improve the quality and effectiveness of care.Aim:To systematically identify health-related quality-of-life outcome measures that could be used in paediatric palliative care and examine their feasibility of use and psychometric properties.Design:A systematic literature review and analysis of psychometric properties.Data sources:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 68 publications
2
67
0
3
Order By: Relevance
“…74,114 Parents of young people report a common range of behaviours in their children: anti-social, disobedient, unwilling to take medication, creating difficulties in incorporating daily medication into their routine schedules, and pill burden associated distress. 40,44,53,86,105,108,117 Adolescents (aged [12][13][14][15][16][17][18] and made it alien to them; some have cited memories of fear that could not be forgotten. 63 Hospitalisation, for treatment, is associated with isolation, affecting opportunities for interaction with friends and siblings, and invoking emotions of sadness, and homesickness.…”
Section: Psychological (N=65 Studies 80%)mentioning
confidence: 99%
See 2 more Smart Citations
“…74,114 Parents of young people report a common range of behaviours in their children: anti-social, disobedient, unwilling to take medication, creating difficulties in incorporating daily medication into their routine schedules, and pill burden associated distress. 40,44,53,86,105,108,117 Adolescents (aged [12][13][14][15][16][17][18] and made it alien to them; some have cited memories of fear that could not be forgotten. 63 Hospitalisation, for treatment, is associated with isolation, affecting opportunities for interaction with friends and siblings, and invoking emotions of sadness, and homesickness.…”
Section: Psychological (N=65 Studies 80%)mentioning
confidence: 99%
“…Measurement of HRQOL will enable those developing and evaluating services to determine their effectiveness. 15 Furthermore, it can enable improvements in clinical care, research, and informed decision making. 16 Currently, there is no appropriate outcome assessment measure for use in paediatric palliative care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review 111 of PPC outcomes concluded that there were no ideal outcome assessment measures for PPC that consistently captured its impact or value. Furthermore, translation of adult-centred measures to paediatric populations is problematic; many adult metrics (eg, assigning of durable power of attorney) are irrelevant in paediatrics, and child and family experiences and psychosocial needs are distinct.…”
Section: The Next Generation Of Ppc Oncology Investigationmentioning
confidence: 99%
“…We read with great interest the recent review of outcome measures in paediatric palliative care (1). This publication in Palliative Medicine is an essential step in advancing the science for this underserved and understudied population.…”
Section: Dear Editorsmentioning
confidence: 99%